The effects of subsidies on the cost structure of Japanese water supply organizations - Takuya Urakami (European Regional Science Association (ERSA), 2004)
The purpose of this study is to identify the effects of subsidies on the cost structure of Japanese water supply organizations by estimating the translog cost function. Geographical conditions, such as network density and water sources, are also controlled in this model. The empirical results indicate that low network density, lack of own water sources and increasing subsidies lead to higher costs. It has also been found that subsidies have caused wasteful use of labor, capital and other input factors, and have diminished scale economies.
Keywords: 330